1991
DOI: 10.1095/biolreprod45.4.547
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of c-kit Protein during Oogenesis and Early Embryonic Development1

Abstract: The c-kit proto-oncogene encodes a transmembrane tyrosine kinase receptor and was shown to be allelic with the white-spotting locus (W) of the mouse. Mutations at the W locus have pleiotropic effects on the development of hematopoietic stem cells, melanoblasts, and primordial germ cells. In order to elucidate the role of c-kit protein in gametogenesis and oocyte maturation, we have examined immunohistochemically the expression of c-kit in the ovaries of mice at late fetal and postnatal stages, and in early emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
86
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(92 citation statements)
references
References 31 publications
6
86
0
Order By: Relevance
“…These results confirm earlier studies showing expression of c-Kit protein in oocytes and expression of its mRNA in oocytes and preovulatory granulosa cells (Horie et al 1993, Tanikawa et al 1998. Although several studies on mice have shown that c-Kit is confined to theca interna cells (Manova et al 1990, Horie et al 1991, Keshet et al 1991, Motro et al 1991, Motro & Bernstein 1993), we did not locate its expression in these cells in human ovarian biopsy samples. In this respect, our result is different from that reported by Ito et al (2001), who used RT-PCR and showed the presence of c-Kit mRNA in human ovarian theca and stroma cells.…”
Section: Discussionsupporting
confidence: 89%
“…These results confirm earlier studies showing expression of c-Kit protein in oocytes and expression of its mRNA in oocytes and preovulatory granulosa cells (Horie et al 1993, Tanikawa et al 1998. Although several studies on mice have shown that c-Kit is confined to theca interna cells (Manova et al 1990, Horie et al 1991, Keshet et al 1991, Motro et al 1991, Motro & Bernstein 1993), we did not locate its expression in these cells in human ovarian biopsy samples. In this respect, our result is different from that reported by Ito et al (2001), who used RT-PCR and showed the presence of c-Kit mRNA in human ovarian theca and stroma cells.…”
Section: Discussionsupporting
confidence: 89%
“…Kit transcripts were absent in both primary and immortalized rat OSE cells and, although Kit expression in other ovarian cell types has been shown to be regulated by various factors including cAMP (Nishina et al, 1992;Ogawa et al, 1995) and human chorionic gonadotropin (Horie et al, 1991), it could not be induced in OSE cells by dbcAMP. Although this observation suggests that Kit does not play a direct role in OSE cell activity, it is equally possible that Kit is important, but is expressed in OSE cells only under speci®c conditions which were not duplicated in culture, or that Kit expression cannot be induced in the immortalized cells used in this study.…”
Section: Discussionmentioning
confidence: 88%
“…Although FSH has not been shown to regulate Kit expression, the LH-like hormone hCG decreases Kit expression in both theca cells and oocytes of mouse ovaries (Motro and Bernstein, 1993;Horie et al, 1991). In addition, both FSH and hCGlike hormones increase KL mRNA expression in granulosa cells of mice (Motro and Bernstein, 1993) and rats (Ismail et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The essential role of SCF/c-Kit in oocyte growth and follicular development has been a topic of investigation for decades [18,19]. c-Kit is expressed at the surface of mammalian oocytes at all stages of follicular development in postnatal ovaries of mice, rats, and humans [20,21], whereas SCF/KL is produced only by granulosa cells [7,22]. In fact, treatment of in vitro cultured follicles from 8-day-old mice with SCF/ KL significantly increased the growth rate of oocytes [23].…”
Section: Discussionmentioning
confidence: 99%